Charge transportation at cascade energy structure interfaces of CuInxGa1-xSeyS2-y/CdS/ZnS for spontaneous water splitting - Chae, Sang Youn; Park, Se Jin; Min, Byong Koun; Hwang, Yun Jeong; Joo, Oh-Shim (PERGAMON-ELSEVIER SCIENCE LTD, 2019)
A photoelectrode has to generate high enough photovoltage by efficient charge separation spontaneously to split water. In this study, cascade band structures with CdS and ZnS applied to CuInxGa1-xSeyS2-y (CIGS) photoelectrode of water splitting. The morphology, the electronic and the chemical state of CIGS heterojunction films have been characterized by a scanning electron microscopy, X-ray photoelectron spectroscopy, and ultraviolet photoelectron spectroscopy. The CIGS/CdS/ZnS photocathode shows similar to 400 mV anodic shift of onset potential and 0.028% efficiency for solar to hydrogen conversion when it couples with a WO3/BiVO4/Co-P-i photoanode for water splitting without external bias potential. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: SOLAR-CELLS; HYDROGEN EVOLUTION; BIVO4 PHOTOANODES; EFFICIENT; PHOTOCATHODES; PERFORMANCE; OXIDE